Seasonal Habitat Use Pattern of Blackbuck (Antelope cervicapra) at Khairapur, Bardia, Nepal - Ban, Suprabha; Singh, Nanda Bahadur (Journal of Natural History Museum, 2015)
The seasonal habitat use pattern of Blackbuck in Blackbuck Conservation Area (BCA) was studied by the division of the realized habitat of Blackbuck (1.74 sq. km) into three blocks A, B and C. Direct count method and indirect count methods were used for the study of seasonal habitat use pattern of the animal. It was observed that block A was mostly used by the animal followed by block C and block B respectively. The study focuses in the implementation of controlled and rotational livestock grazing in BCA as an effective wildlife management tool. J. Nat. Hist. Mus. Vol. 26, 2012: 224-229